1993
DOI: 10.1172/jci116667
|View full text |Cite
|
Sign up to set email alerts
|

Induction of humoral and cell-mediated anti-human immunodeficiency virus (HIV) responses in HIV sero-negative volunteers by immunization with recombinant gp160.

Abstract: Development of an effective vaccine for prevention of infection with HIV would provide an important mechanism for controlling the AIDS epidemic. In the current study, the first clinical trial of a candidate HIV-1 vaccine initiated in the United States, the safety and immunogenicity of escalating doses (10-1,280 Aig) of recombinant gp160 (rgpl6O), were evaluated in 138 HIV-negative volunteers. Maximal antibody responses, as evaluated by ELISA, were seen after immunization with three doses of 1,280 ;&g rgpl6O. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…Other studies of rgp160 have collected similar data in both HIV-1-infected and uninfected persons [11,[14][15][16][17], confirming the immunogenicity of this recombinant gp160 vaccine. The responses to rgp160 were maintained throughout the study, with some diminution in year 4 and 5, showing the ability of the immune system in HIV-1-infected persons to sustain a proliferative response.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Other studies of rgp160 have collected similar data in both HIV-1-infected and uninfected persons [11,[14][15][16][17], confirming the immunogenicity of this recombinant gp160 vaccine. The responses to rgp160 were maintained throughout the study, with some diminution in year 4 and 5, showing the ability of the immune system in HIV-1-infected persons to sustain a proliferative response.…”
Section: Discussionsupporting
confidence: 68%
“…After a series of vaccinations with a recombinant HIV-1 envelope protein (rgp160) or a whole inactivated HIV-1 preparation, HIV-1-infected persons were able to mount new proliferative responses to envelope proteins and/or new delayed-type hypersensitivity responses, as well as novel epitope-specific antibody responses, compared with natural history cohorts [10]. The same recombinant protein was also tested in HIV-1-seronegative persons in phase I trials and was shown to be safe and immunogenic [14][15][16][17].…”
mentioning
confidence: 99%
“…The question now arises of whether this defective lymphocyte response is the result of a limited immunogenicity of the virus or of a loss of the specific response during the course of disease. Much evidence allows one to rule out the first hypothesis: (i) HIV-specific T lymphocytes are present in the repertoire of healthy HIV" individuals, and can be readily activated in vitro hy repeated stimulations with antigen-pulsed APC[I8];(ii) proliferative response to gpI60 is easily detected in healthy volunteers immunized with gpI60 itself [19,20]; (iii) HIVspecific T heiper responses, detected both as IL-2-specific release and proliferation, have been reported in HIV individuals exposed to H1V and possibly protected from full infection by the development of such a response [21][22][23][24]; (iv) in vitro proliferative responses to HIV peptides can be restored by IL-12 [25]. Taken together, these findings suggest that HIV-specific T helper ceils undergo early inactivation (functional anergy rather than depletion), possibly through a preferential exposure to virus contained In specific APC.…”
Section: Discussionmentioning
confidence: 99%
“…HIV infection of chimpanzees and simian immunodeficiency virus (SIV) infection of rhesus macaques are widely used as models for HIV vac cine research. From a scries of successful active and pas sive immunisation experiments, protection in chimpan zees from HIV infection seems to be associated with an antibody response to the viral envelope glycoprotein [1][2][3][4][5], Detailed analysis of the chimpanzees' antibody re sponse revealed that a considerable portion of neutralis ing antibodies is directed to conformational and highly conserved epitopes of the gpl20 external glycoprotein in addition to the isolate-specific V3 domain [6], However, the chimpanzee model should not be overstressed as the capability of HIV to replicate in chimpanzees is limited and therefore a cryptic type of immune response might be sufficient to confer a sterilising immunity. In addition, as chimpanzees neither develop a substantial HIV-specific cytotoxic T lymphocyte (CTL) response nor AIDS-like symptoms following infection with HIV, the use of this animal model in clarifying the type of immune response, which mediates protections, is limited.…”
Section: Introductionmentioning
confidence: 99%